Snapshot of Poverty and Labor Market Outcomes in Lebanon Based on Household Budget Survey 2011-2012 - Central Administration for Statistics; World Bank Group (World Bank, Washington, DC, 2016)
This brief is based on analysis of the 2011-12 household budget survey (HBS) implemented by Central Administration for Statistics (CAS) with technical assistance from the World Bank. The survey was conducted during the period of September 2011 to November 2012, and was stratified across nine regions. The sample was designed to cover 4,805 households, but due to high non-response, it only includes 2,476 participating households. Poverty numbers presented in this note are not comparable with poverty estimates for other years due to differences in the instruments, fieldwork implementation and to some extent sample design; and also due to differences in the methodology for constructing welfare aggregate and the poverty line. All regional estimates in this report should be viewed with caution given concerns about significant levels of nonresponse and relatively small sample sizes within regions. CAS and the World Bank are working together to improve the quality of future surveys.